Host preference in isolates of Phytophthora infestans collected from potato and tomato crops in Colombia (2018)
The plant pathogen Phytophthora infestans is the causal agent of late blight disease in both potato (Solanum tuberosum) and tomato (Solanum lycopersicum) crops. Previous studies suggest that isolates of P. infestans present differences in their potato-tomato host preference. In Colombia, potato and tomato are economically important. Thus, it is important to determine if populations of P. infestans growing on potato may pose a risk to nearby tomato crops and vice versa. To achieve this, detached leaflets from one susceptible variety of potato (Diacol Capiro) and detached leaflets from one susceptible variety of tomato (Chonto Santa Cruz Kada), were inoculated with six isolates of P. infestans collected from potato and six isolates of P. infestans collected from tomato from different rural areas of Colombia. Two isolates from the United States, with known host preference, were used as controls. Lesion area and mean sporulation between the two hosts were determined seven days after inoculation for all isolates. Furthermore, the incubation period and latent period on potato and tomato were also evaluated. The results suggest that isolates that had been collected on potato could represent a risk for nearby tomato crops. However, most isolates that had been collected on tomato did not grow on potato. Information on the potato-tomato host preference of isolates of P. infestans in Colombia may be important for future field-management decisions